The Minimum Age of Criminal Responsibility: The Need for a Holistic Approach’ - Anthony Charles (Youth Justice, 2021)
The minimum age of criminal responsibility, as currently established within England and Wales, remains ten years of age. Despite criticism of the minimum age of criminal responsibility, the Westminster Government is unwilling, in spite of research evidence and growing distance between its and international visions of an acceptable threshold, to countenance change. Drawing upon the views of the United Nations Committee on the Rights of the Child and the activities of devolved administrations within the UK, this article explores the need for change to be made to the minimum age of criminal responsibility and considers how holistic approaches, based upon diversion and rights respecting appropriate interventions can create transformative outcomes for children who come into contact with the law.